Implementation of the Flipped Classroom Model to Improve Student Learning Outcomes - Tomasouw, Jolanda; Marantika, Juliaans E. R.; Que, Stella R.; Van Delzen, June C. Noya (Nexus Publishing, 2024)
This study investigates how implementing the Flipped Classroom model can improve high school students' German language learning outcomes at Lab Unpatti High School. The Flipped Classroom is a blended learning approach combining face-to-face interaction with online activities, integrating synchronous (real-time) learning with asynchronous (self-paced) study. This model moves the initial information delivery outside the classroom, allowing class time to be used for deeper knowledge assimilation. The study involved 24 tenth-grade students from Lab Unpatti High School. An experimental method with a one-group pre-test and post-test design was employed. Data collection instruments included tests and questionnaires. Data analysis using a t-test showed that the calculated t-value (5.055) significantly exceeded the t-table value (1.710). This significant difference indicates a substantial improvement in learning outcomes, with students' average German scores increasing by over 89%. Therefore, it can be concluded that the Flipped Classroom model effectively enhances students' learning outcomes.